2022
DOI: 10.1080/26410397.2021.2009104
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and provision of self-care interventions for sexual and reproductive health: findings from a global values and preferences survey

Abstract: Self-care interventions hold the potential to improve sexual and reproductive health (SRH) and well-being. Yet key knowledge gaps remain regarding how knowledge and uptake vary across different types of self-care interventions. There is also limited understanding of health workers’ confidence in promoting SRH self-care interventions, and how this may differ based on personal uptake experiences. To address these knowledge gaps, we conducted a web-based cross-sectional survey among health workers and laypersons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…In a global survey of values and preferences in relation to self-care interventions, Logie and colleagues found that privacy, confidentiality and accessibility were more important considerations in the use of self-care interventions than empowerment. 7 Privacy was also found to be important to women using telehealth abortion services in Chile. 18 The need to ensure privacy in self-care interventions is underscored by the findings of one of the papers in Burke and colleagues’ review of reproductive empowerment and self-care in family planning, which found that a client-facing digital technology intervention inadvertently increased experiences of physical violence.…”
Section: Right To Privacymentioning
confidence: 99%
See 2 more Smart Citations
“…In a global survey of values and preferences in relation to self-care interventions, Logie and colleagues found that privacy, confidentiality and accessibility were more important considerations in the use of self-care interventions than empowerment. 7 Privacy was also found to be important to women using telehealth abortion services in Chile. 18 The need to ensure privacy in self-care interventions is underscored by the findings of one of the papers in Burke and colleagues’ review of reproductive empowerment and self-care in family planning, which found that a client-facing digital technology intervention inadvertently increased experiences of physical violence.…”
Section: Right To Privacymentioning
confidence: 99%
“…The importance of linkage to the health system and the valuable role of health workers were highlighted across many of the articles in this issue, and additional attention to how this might best be achieved would be useful. 7–10 Logie and colleagues noted that the preferred location for accessing self-care interventions varied by the type of self-care intervention, with most respondents preferring to access them either from a doctor or at a pharmacy. 7 The need for choice in where, how and from whom to access self-care interventions was repeatedly underscored.…”
Section: Safeguards To Enhance Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…Reflecting on SRH, among the various aspects of personal health that require self-care education, is thus of utmost importance in the public and SRH health intervention programs [ 7 ]. As well, self-care interventions can improve SRH and well-being [ 8 ], but It seems individuals usually do not meet their needs for improving SRH status and receiving self-care skills from professionals and healthcare providers (HCPs), but mostly prefer to go to pharmacies and purchase modern medications, and the like [ 9 ]. In this way, sexual health has been recognized as one of the important health topics, as many women suffer from various sexually transmitted diseases (STDs), such as acquired immunodeficiency syndrome, vaginal infections (or vaginitis), gastrointestinal diseases, skin disorders, etc.…”
Section: Introductionmentioning
confidence: 99%
“…We all are seeing an increase in momentum in terms of the use of digital health solutions to enable pregnant women to perform self-care interventions (3)(4)(5). Although self-care interventions offer innovative and equitable ways to improve maternal health outcomes (6), the uptake of self-care interventions among pregnant women is low, especially in lowmiddle-income countries (7). Notably, pregnant women need to have a self-care agency to perform self-care interventions throughout pregnancy (8).…”
mentioning
confidence: 99%